Momentum-resolved resonant inelastic soft X-ray scattering (qRIXS) endstation at the ALS - Chuang, Yi-De; Feng, Xuefei; Cruz, Alejandro; Hanzel, Kelly; Brown, Adam; Spucces, Adrian; Frano, Alex; Lee, Wei-Sheng; Kim, Jaemyung; Chen, Yu-Jen; Smith, Brian; Pepper, John S.; et al. (Journal of electron spectroscopy and related phenomena, 2022)
•An endstation with multiple modular soft X-ray spectrometers for parallel detection.•Capable of operating at different beamlines at synchrotrons and FEL facilities.•Enabling momentum-resolved RIXS spectroscopy at the ALS.•High throughput RIXS spectroscopy for energy and quantum materials research. A momentum resolved resonant inelastic X-ray scattering (qRIXS) experimental station with continuously rotatable spectrometers and parallel detection is designed to operate at different beamlines at synchrotron and free electron laser (FEL) facilities. This endstation, currently located at the Advanced Light Source (ALS), has five emission ports on the experimental chamber for mounting the high-throughput modular soft X-ray spectrometers (MXS) [24]. Coupled to the rotation from the supporting hexapod, the scattered X-rays from 27.5° (forward scattering) to 152.5° (backward scattering) relative to the incident photon beam can be recorded, enabling the momentum-resolved RIXS spectroscopy. The components of this endstation are described in details, and the preliminary RIXS measurements on highly oriented pyrolytic graphite (HOPG) reveal the low energy vibronic excitations from the strong electron-phonon coupling at C K edge around σ* band. The grating upgrade option to enhance the performance at low photon energies is presented and the potential of this spectroscopy is discussed in summary.